Adaptation and Integration of Labour Migrants from Central Asia in Russia and Countries of European Union: Comparative Analysis - Bedrina, Elena B.; Lazareva, Elena V. (Economy of Regions, 2021)
Currently, the Russian Federation is experiencing a transformation of migration flows from temporary to permanent. The largest share of migrants comes from the countries of Central Asia, where the demographic and economic situation stimulates a long-term increase in flows of labour migrants. In these conditions, it is necessary to examine issues of adaptation and integration of migrants. We review scientific literature on the adaptation practises of labour migrants. We applied the method of comparative analysis due to the importance the accumulated experience of European countries, which chose a policy of active integration. We analysed scientific publications, which are indexed in Scopus, Web of Science, E-library databases, and focused on the factors and models of adaptation of labour migrants from Central Asia in Russia and the countries of the European Union (EU). The study revealed the growing interest in the research topic, increased publication activity and joint research by representatives of different countries. In most cases, researchers note the role of social capital in the adaptation of migrants, the length of the acculturation process of migrants and the importance of participation of the host community in the process. We proposed to consider the experience of bilateral adaptation in the EU countries. As the flow of migrants to the EU countries from Central Asia increases, the interest in this topic on the part of Western researchers will grow. The research results can be used to improve efficiency in the research of migration processes.